Spanish teachers’ representations about the textbook - Abdalla, Glória Cortés (The ESPecialist, 2014)
This paper aims to reveal Spanish teachers’ representations related to the textbook and to discuss the reason for its selection, adaptation and use as one of the materials in foreign language teaching. The study was developed in two stages: data was collected with students from a Spanish teacher education course in 2009 and in 2011. Results show the importance of developing awareness in pre-service and in-service teacher education about the choice of textbooks.